Oral transmission of Trypanosoma cruzi, Brazilian Amazon - Santana, Rosa Amélia G. (2021)
In the Brazilian Amazon, the suspected source of infection in an outbreak of acute Chagas disease involving 10 patients was Euterpe oleracea (açaí berry) juice. Patient blood and juice samples contained Trypanosoma cruzi TcIV, indicating oral transmission of the Chagas disease agent.